Effect of PGPM and goat manure doses on biomass yield and rosmarinic acid content in cat's whiskers plant (Orthosiphon aristatus Bl. Miq) - Ima Mulyama Zainuddin; Millennio Salsabil; Mohammad Ghifary Muktabar; Dadang Sumardi (Current Research on Bioscences and Biotechnology, 2023)
Cat’s whiskers plant (Orthosiphon aristatus B. Miq) is a medicinal plant containing various metabolites that act as antioxidants and anti-inflammatory, including rosmarinic acid. The domestic market demand for dry leaves was 20-40 tons and abroad it was 141-180 tons in the 1990-2005 period, while production from 2013 to 2017 decreased from 116 tons to 56 tons. Therefore, it is necessary to increase the cat's whiskers biomass production, one of which can be done through the engineering of growing media using organic fertilizers, including goat manure and microbes, e.g., Plant Growth Promoting Microorganisms (PGPM). This study aims to determine the optimal combination of PGPM – Goat Manure for biomass and the rosmarinic acid content in O. aristatus. The study was conducted using a 2-factor randomized block design (RBD) with 12 treatment combinations and 3 repetitions on cultivated land in the Tanjungsari area and analysis of the results was carried out in the SITH laboratory from October 2020 to March 2021. The rosmarinic acid content in the leaves ranged from 144.43 – 206.31 mg/g or 14.44 – 20.63%, with the highest content found in leaves treated with 3 ml/L PGPM and 86.2 g/plant goat manure fertilizer (P2O2).